A right to die? - Walker, Richard (New York : Franklin Watts, 1997)
Discusses the moral and ethical aspects of euthanasia and related topics.
Includes index.
Wilson's Junior High School
School Library Journal
Science Books & Films (A.A.A.S.)
7.3
5-8
Keywords: Right to die -- Juvenile literature; Euthanasia -- Juvenile literature; Assisted suicide -- Juvenile literature; Medical ethics -- Juvenile literature; Right to die; Euthanasia; Assisted suicide; Suicide; Right to die; Euthanasia; Suicide; Medical ethics